EFFECT OF SACCHAROMYCES CEREVISIAE ADDITION TO FEED ON THE GROWTH AND MICROBIAL COMMUNITY PROFILE IN THE DIGESTIVE TRACT OF BROILER CHICKENS (GALLUS DOMESTICUS) - Laila Hayatin, Salwa
Chicken meat is often regarded as the predominant source of animal protein for the Indonesian, enjoying significant popularity among the local population. However, small enterprise farmer encounter difficulties during chicken production as a result of the restriction imposed by the authority on the utilization of antibiotic growth promoters (AGPs) in animal feed. The AGPs serves in controling the population of harmful microorganisms in the gastrointestinal tract and facilitating optimal growth and development of the chicken. Given the circumstances, it is important to develop an alternate approach that may effectively substitute antibiotics in the chickens feed. The aim of this study is to investigate the influence of Saccharomyces cerevisiae supplementation in the chicken feed on the growth and the composition of microbial communities in chicken small intestines. The experiment was carried out by implementing three treatment variations, i.e: 0% supplementation of S. cerevisiae (w/w), 0,2% supplementation of S. cerevisiae (w/w), and 0,4% supplementation of S. cerevisiae (w/w) to the feed. Body weight were recorded daily over a 35-day course of experiment. At the end of the experiment, the chickens were sacrificed and detailed examinations were conducted on the intestines, liver, and gizzards. Furthermore, samples of small intestine content were collected and analysed for 16S rRNA gene sequencing. It was found that the weight of chickens carcass raised on diets containing 0%, 0,2%, and 0,4% S. cerevisiae comparatively were insignificant, measuring at 358,00 gr, 306,50 gr, and 392.00 gr respectively. Further data analysis on the growth of the chicken, shows that the chicken raised on 0%, 0,2%, and 0,4% S. cerevisiae containing diets exhibited an average of growth rates of 0,0933/day, 0,0901/day, and 0,1041/day, respectively. Furthermore, it was also found that the chicken which were raised with 0%, 0,2%, and 0,4% S. cerevisiae supplementation was found to have relative intestine length of 0,18733 cm (cm/gr body weight), 0,18634 cm (cm/gr body weight), and 0,22336 cm (cm/gr body weight) respectively. It was also found that the chicken fed with 0%, 0,2%, and 0,4% S. cerevisiae exhibits the liver-to-body weight and gizzard-to-body weight of of 0,02816 (gr/gr body weight) and 0,04049 (gr/gr body weight), 0,02580 (gr/gr body weight) and 0,0385 (gr/gr body weight). Based on the aforementioned findings, it can be said that S. cerevisiae supplementation has no adverse effects on chicken growth or the development of the gut, gizzard, or liver. DNA sequencing of small intestine samples reveal that S. cerevisiae supplementation reduce the presence of Proteobacteria and Chlamydiae and promote the growth of Firmicutes. The result indicates that supplementation of Saccharomyces cerevisiae reduces the presence of pathogenic bacteria belong to Proteobacteria and Chlamydiae, such as Escherichia coli, Campylobacter jejuni and Salmonella sp.